Athletics in extreme cold: Dos and don'ts - Campbell, J. D.; Sebastianelli, W. J. (Sports Medicine Update, 2007)
Participating athletically in cold, inclement weather can be a challenge. Athletes as well as caregivers can be subjected to significant thermal risk. In this connection this article is on - Types of cold, - Loss of body heat, - Cold weather first aid, - Clothing tips and - Altitude.